The Effect Of Baby Spa Education On Mothers' Interest In Implementing Baby Spa At Pmd Ida Laina Bengkulu City In 2023 - Wanti , Sindi Silviya; Yulianti , Syami; Darmawansyah, Darmawansyah (Multidisciplinary Journals, 2025)
Infants are children aged 0-12 months. The infant period is the first critical stage of life. The purpose of this study was to determine the effect of baby spa counseling on mothers' interest in implementing baby spa at PMB Ida Laina, Bengkulu City, in 2023.The research method used was a pre-experimental design with a one-group pre-test post-test design. The sampling technique used in this study was purposive sampling with a sample size of 32 respondents. Data collection involved the entire population of mothers with infants aged 0-12 months at PMB Ida Laina Bengkulu City. Data collection included editing, scoring, coding, and tabulating. The instrument used was a questionnaire. The results of the study on mothers' interest in the implementation of Baby Spa at PMB Ida Laina in Bengkulu City showed that 32 respondents indicated a high level of interest. High 22 (68.7%), moderate 6 (18.7%), low 4 (12.5%). And mothers' interest in implementing Baby Spa after counseling was high 31 (96.9%), moderate 1 (3.1%). Conclusion: There is an effect of Baby Spa counseling on mothers' interest in the implementation of Baby Spa at PMB Ida Laina in Bengkulu City.